Interprofessional communication between doctors and nurses in a tertiary hospital / Norazizi Nor Azmi - Norazizi , Nor Azmi (2024)
Effective interprofessional communication is essential in healthcare settings, particularly in the fast-paced and high-stakes environment of the operating theatre. However, little is known about how nurses perceive the communication between anaesthetic nurses and anaesthetic doctors in this setting. This research aims to explore and understand the perception of nurses regarding interprofessional communication between anaesthetic nurses and anaesthetic doctors in the operating theatre. The research project was conducted as an online, self-administered questionnaire, in a tertiary hospital in Kuala Lumpur, involving anaesthetic nurses working in the operating theatre. The study concluded that whilst professional interactions, competence, mutual respect and trust are satisfactory, there is much left to be desired for teamwork and the workplace atmosphere (having the lowest mean variables = 3, compared to other dimensions). The findings of this research can guide the development of training programs and interventions to improve interprofessional communication in the operating theatre, ultimately leading to enhanced patienty safety, quality of care and staff satisfaction.